Peatland Fungal Community Responses to Nutrient Enrichment: A Story Beyond Nitrogen - Wang, Meng; Lamit, Louis J.; Lilleskov, Erik A.; Basiliko, Nathan; Moore, Tim R.; Bubier, Jill L.; Guo, Galen; Juutinen, Sari; Larmola, Tuula (Global change biology, 2024)
ABSTRACT Anthropogenically elevated inputs of nitrogen (N), phosphorus (P), and potassium (K) can affect the carbon (C) budget of nutrient‐poor peatlands. Fungi are intimately tied to peatland C budgets due to their roles in organic matter decomposition and symbioses with primary producers; however, the influence of fertilization on peatland fungal composition and diversity remains unclear. Here, we examined the effect of fertilization over 10 years on fungal diversity, composition, and functional guilds along an acrotelm (10–20 cm), mesotelm (30–40 cm), and catotelm (60–70 cm) depth gradient at the Mer Bleue bog, Canada. Simultaneous N and PK additions decreased the relative abundance of ericoid mycorrhizal fungi and increased ectomycorrhizal fungi and lignocellulose‐degrading fungi. Fertilization effects were not more pronounced in the acrotelm relative to the catotelm, nor was there a shift toward nitrophilic taxa after N addition. The direct effect of fertilization significantly decreased the abundance of Sphagnum‐associated fungi, primarily owing to the overarching role of limiting nutrients rather than a decline in Sphagnum cover. Increased nutrient loading may threaten peatland C stocks if lignocellulose‐degrading fungi become abundant and accelerate decomposition of recalcitrant organic matter. Additionally, future changes in plant communities, strong water table fluctuations, and peat subsidence after long‐term nutrient loading may also influence fungal functional guilds and depth‐dependencies of fungal community structure. Fungi can break down recalcitrant organic matters but how nutrient loading affects their composition and diversity in nutrient‐poor peatlands is not well understood. Our long‐term fertilization experiments found that adding nitrogen, phosphorus, and potassium reduced the abundance of ericoid mycorrhizal fungi and increased ectomycorrhizal fungi and lignocellulose‐degrading fungi. These effects were similar between different peat depths. The reduced abundance of Sphagnum‐associated fungi was primarily owing to the overarching role of limiting nutrients rather than a decline in Sphagnum cover. Changes in plant communities and peat subsidence after long‐term nutrient loading may threaten carbon storage in peatlands.